Reduced Tic Symptomatology in Tourette Syndrome After an Acute Bout of Exercise: An Observational Study. (March 2014) - Nixon, Elena; Glazebrook, Cris; Hollis, Chris; Jackson, Georgina M.
In light of descriptive accounts of attenuating effects of physical activity on tics, we used an experimental design to assess the impact of an acute bout of aerobic exercise on tic expression in young people ( N = 18) with Tourette Syndrome (TS). We compared video-based tic frequency estimates obtained during an exercise session with tic rates obtained during pre-exercise (baseline) and post-exercise interview-based sessions. Results showed significantly reduced tic rates during the exercise session compared with baseline, suggesting that acute exercise has an attenuating effect on tics. Tic rates also remained reduced relative to baseline during the post-exercise session, likely reflecting a sustained effect of exercise on tic reduction. Parallel to the observed tic attenuation, exercise also had a beneficial impact on self-reported anxiety and mood levels. The present findings provide novel empirical evidence for the beneficial effect of exercise on TS symptomatology bearing important research and clinical implications.